Interlanguage syntax of L2 Persian speakers: the case of resumptive pronouns in English relative clauses - Enjavinezhad, Maryam; Paramasivam, Shamala (Contemporary Research Center Australia, 2014)
Whether UG is accessible to L2 learners, or whether L2 acquisition is constrained by Universal Grammar (UG) has been a debatable issue among researchers. Schwartz and Sprouse (1996)suggested the Full Transfer Full Access hypothesis (FTFA), in which the initial state of L2 is considered L1 grammar, and L2 learners are believed to have full access to UG. Therefore, parameter resetting is considered possible. This study was an attempt to investigate the development of the interlanguage grammar of Persian speakers acquiring English as a second language at different proficiency levels, and specifically focused on English relative clauses, in the light of FTFA hypothesis. The syntactic parameter under investigation was resumptive pronouns (RPs). While RPs are generally disallowed in English relative clauses, the use of an RP in the Persian counterparts is perfectly acceptable and required. Therefore, in the case of resumptive pronouns available in the L1(Persian) but not in the L2 (English), the prediction was that the Persian learners of English language would have problems in abandoning the resumptive strategy in L2 clause. A grammaticality judgment task was given to two groups of adult Persian speakers acquiring English as a second language (advanced and intermediate groups) and the tendencies within the two groups on the grammaticality judgement task fitted well with the predictions made by the 'full transfer' claim of the FTFA. Also, it was found that advanced L2ers can successfully reconstruct their grammar according to the L2 setting.